Perbandingan Profile Stabilitas Sediaan Suspensi Berbasis Ekstrak Alami Dan Bahan Kimia Sintesis - Nissa, Hayatun; Rahmah, Elita; Latifah, Nor (STIKes Ibnu Sina Ajibarang, 2025)
The stability profile of suspension formulations is a critical factor in determining the shelf life, efficacy, and safety of pharmaceutical products. This review compares the stability of suspensions based on natural extracts and those formulated with synthetic chemicals. The objective is to explore the physicochemical behavior of both types, with attention to sedimentation rate, particle size distribution, viscosity, and pH variation over time. This literature-based analysis employs a comparative method using previously published experimental data on various suspension formulations. The findings indicate that while synthetic-based suspensions often demonstrate superior stability due to controlled formulation variables, natural extract-based suspensions can achieve acceptable stability through the use of proper suspending agents and preservation techniques. The implication of this comparison is to provide formulators with a balanced perspective when choosing between natural and synthetic ingredients for suspension development, especially in the context of clean-label and green pharmacy trends.